PEMANFAATAN PEMASARAN ONLINE PENJUAL TELOR ASIN DI KABUPATEN KARAWANG - Jaenal Aripin; Hawignyo . (STKIP PGRI Jombang, 2022)
Marketing is very important for all businesses, regardless of whether the business is big or small. If in a business there is no marketing, then consumers will not know about a product produced from the business and make sales low. In the era of technology that continues to develop rapidly as it is today, the marketing model can apply a technology that can quickly and can reach wider consumers in a short time and of course with marketing funds that are not too large. A seller can apply a marketing method by utilizing a more efficient and inexpensive electronic media, namely the internet. The purpose of this study is to determine the strategy of selling salted eggs in Karawang district through online marketing. This study uses a descriptive method with a qualitative approach. The number of population and samples in this study were 20 salted egg traders in the cilamaya kulon and cilamaya wetan sub-districts who had used online media. This research was conducted by conducting interviews with several informants. The results of this study are salted egg producers in Karawang Regency have done a good online marketing system, where all stages of the process in the promotion mix activities. Manufacturers have carried out online advertising, sales promotion, direct marketing, and personal selling well. Salted egg marketers need to maintain and improve online marketing models with trained individuals, so they can take full advantage of online media including websites, blogs and social media.